Halogenases of Qarhan Salt Lake in the Qaidam Basin: Evidence From Halite Fluid Inclusions - Li, Jun; Zhang, Xiying; Hu, Mingyue; Li, Wenxia; Miao, Weiliang; Yuan, Xiaolong; Li, Yongshou; Tang, Qiliang; Han, Wenxia; Ma, Haizhou (Frontiers in Earth Science, 2021)
The fluid inclusion composition of halite can help track chemical composition of ancient fluids, and thus serves as a reliable index to analyze ancient brine in salt lakes. The Qarhan Salt Lake (QSL) is the largest potash brine deposit in China. Although the mixing of modern river water and Ca-Cl deep water is widely accepted as the potassium formation, the mixing characteristics in time dimension and driving factors of deep water are still unclear. Here, the chemical composition of fluid inclusions in primary halite samples collected from ISL1A borehole in QSL was measured by LA-ICP-MS technology. The analysis results show that during the formation stage of the S4 salt layer in QSL, the main potassium salt layer, the contents of Ca2+ and Sr2+ in brine increased significantly. There is evidence confirm that Ca-Cl deep water is beneficial to the enrichment of potassium, and the surrounding rivers generally developed terraces. It suggests that during the formation stage of QSL potassium salt layer, more Ca-Cl inflow water of the northern margin supplies the salt lake, and inferred that it was driven by tectonic activities. In addition, the chemical composition of halite fluid inclusions shows that there is an anomaly in geochemistry at the early stage of salt formation in QSL. By combing the time of tectonic activities, it is inferred that the anomaly is not caused by tectonic activitiest, may be it was caused by a salt-forming event. This work indicate that deep water and tectonic movement have a heavy impact on the evolution of salt lakes. Therefore, it is necessary to consider the influence of deep water and tectonic activities on salt-forming evolution of salt lakes when studying salt-forming evolution of salt lakes and paleoclimate by using core profiles.